2023
DOI: 10.1088/1572-9494/acdce5
|View full text |Cite
|
Sign up to set email alerts
|

Tsallis relative α entropy of coherence dynamics in Grover′s search algorithm

Abstract: Quantum coherence plays a central role in Grover's search algorithm. We study the Tsallis relative $\alpha$ entropy of coherence dynamics of the evolved state in Grover's search algorithm. We prove that the Tsallis relative $\alpha$ entropy of coherence decreases with the increase of the success probability, and derive the complementarity relations between the coherence and the success probability. We show that the operator coherence of the first $H^{\otimes n}$ relies on the size of the database $N$, the succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…It is found that the overall effect in Grover's search algorithm is that the l 1 norm of coherence is depleted during the quantum search process [68], and the complementarity relation between the success probability and coherence has been derived [69]. Following the idea in [68,69], coherence dynamics in Grover's search algorithm has been studied based on Tsallis relative α entropy [70]. Recently, Feng, Chen and Zhao have studied coherence and entanglement in Grover and HHL algorithm [71].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the overall effect in Grover's search algorithm is that the l 1 norm of coherence is depleted during the quantum search process [68], and the complementarity relation between the success probability and coherence has been derived [69]. Following the idea in [68,69], coherence dynamics in Grover's search algorithm has been studied based on Tsallis relative α entropy [70]. Recently, Feng, Chen and Zhao have studied coherence and entanglement in Grover and HHL algorithm [71].…”
Section: Introductionmentioning
confidence: 99%